The Effect of Element Types on Force Analogy Method Analysis - Iraj Toloue; Mohd Shahir Liew; Indra Sati Hamonangan Harahap (Journal of Engineering and Technological Sciences, 2017)
In this study, the seismic performance of a 2D portal frame subjected to the recorded seismic ground motions of the Northridge 1994 earthquake was evaluated by the force analogy method (FAM) with different element types. To increase the accuracy of FAM, Timoshenko (TS) elements were employed instead of the classical Euler Bernoulli (EB) elements, to revert the shear deformations that are neglected in EB elements. To perform evaluation, the same material and section properties were considered and the same portal frame was analyzed with different element lengths, from 0.5 to 7.0 m in 0.5 m steps.